Evaluation of the Strength Of R60 Type Rails Against Loading High-Speed Trains - Septa Ade Dermawan; Nunung Widyaningsih (International Journal Labs, 2024)
Currently, Indonesia has entered a new phase in the development of modern transportation infrastructure, namely high-speed trains initiated by PT Kereta Cepat Indonesia China. The design of the facility operated is an Electrical Multiple Unit (EMU) CR400AF that can drive up to speeds of 350 km / h. Of course, high train speed requires the reliability of railway road infrastructure, including the geometry and components of rail roads. The technical specifications of high-speed rail roads have been regulated in the Minister of Transportation Regulation Number 7 of 2022. The type of rail used by high-speed railway line components with a rail road width of 1435 mm is type R60 rail. However, the determination of the type of high-speed railway in Indonesia has not been completed by analyzing the strength of the rail structure in bearing the load working on it. Thus, this study discusses the influence of rail road geometry on the speed of facilities and evaluates the strength of Type R60 rail structures in receiving high-speed train loads. The analysis method uses the Beam on Elastic Foundation (BOEF) method which assumes the behavior of rails as continuous beams that receive loads on elastic foundation pedestals. The results of the study found that the value of the realized radius and minimum radius of the horizontal arch respectively amounted to 9,500 m and 8,502.94 m greater than the horizontal arch permit radius of 7,000 m, while for the value of the permit radius and vertical radius of the vertical arch of 25,000 m. So that the optimization of the horizontal curved radius to 8,502.94 m to be more in line with the ability of the path to serve passing facilities and is expected to be more effective and efficient in planning. The static load and dynamic load of the EMU wheel CR400AF of 81,662.50 N and 243,522.90 N. The maximum voltage and rail clearance voltage were obtained at 134.53 N/mm2 and 228.57 N/mm2. The strength of the rails is written in the form of a safety factor (SF) number. The calculation results show that the most critical SF value of the rail in receiving the load of high-speed trains is 1.70. Based on the results of BoEF calculations, R60 type rails have a high safety value in withstanding static loads and dynamic loads of high-speed trains.